Neurofibromatosis Type 2 Involving the Brain and Spinal Cord - O. A. Staroseltseva; N. V. Nudnov; M. L. Radutnaya; I. G. Shchelkunova; A. A. Yakovlev; A. N. Vorobyev; A. N. Kirchin (Вестник рентгенологии и радиологии)
Neurofibromatosis type 2 is a rare genetic disease that occurs with a frequency of approximately 1 in 50,000 newborns and is characterized by benign tumors, mainly bilateral schwannomas of the VIII cranial nerve. It is inherited by an autosomal dominant type without sex. Clinical symptoms are associated with damage to the VIII pair of cranial nerves, skin manifestations are less common than with neurofibromatosis type 1. The tumor can be one-sided and can be combined with neurofibromas, meningiomas (intracranial and spinal), schwannomas of other cranial nerves, astrocytomas and ependymomas of the spinal cord. In detecting tumors and making a primary diagnosis, the leading role is played by instrumental diagnostic methods: magnetic resonance imaging (MRI) and computed tomography (CT). The final diagnosis is made after genetic analysis. The article presents the possibilities of CT and MRI in imaging and  diagnosis of type neurofibromatosis type 2.